Ecological trait evolution in amphibian phylogenetic relationships. Issue 6 (2nd November 2019) - Campos, Felipe S.; Lourenço-De-Moraes, Ricardo; Rudoy, Andrey; Rödder, Dennis; Llorente, Gustavo A.; Solé, Mirco
Abstract : Current biodiversity patterns of Neotropical amphibians are the result of their functional and phylogenetic relationships. Understanding the associations between ecological similarity and phylogenetic relatedness among species can provide a convincing statement on the role of evolutionary history in the filling of the niche space. Here, we assessed the ancestral character states of amphibian ecological traits and their evolutionary history in the Atlantic Forest Hotspot. We used 12 genes (11, 906 bp) to reconstruct a phylogeny for 207 amphibian species and related it to eight ecological traits regarding their morphology, life-history and behavioural features. We revealed that closely related species can have similar ecological traits, suggesting that these traits are driven by phylogenetic history. Despite the high endemism rate of Atlantic Forest amphibians, our findings heavily rely on good studies on complete amphibian phylogenetic lineages to overcome potential biogeographical constraints. Using mechanisms of adaptive evolution in the context of phylogenetic diversification, we suggest that closely related species have different phylogenetic signals and ecological traits can evolve without relatedness.